The synthesis of Diarylisobenzofuran and Adamantylidene probes for the selective detection of singlet oxygen in plasma - James Fuster (2022)
A set of highly fluorescent probes based on diphenylisobenzofuran (DPBF) have been synthesized and applied in a plasma COST jet for the detection of singlet oxygen (1O2), a reactive species vital for both synthetic applications and as a marker for cytotoxicity. The mechanistic understanding of singlet oxygen is limited due to its short lifetime (14 μs in ethanol). The research in this thesis showed that the highest concentration of singlet oxygen produced in plasma (150 V) was achieved using a 0.75% admixture of oxygen. The addition of electron donating groups (EDGs) within the aromatic ring illicited a faster probe response compared to DPBF. The utilisation of Hammett plots revealed that the mechanism for reacting with singlet oxygen was dependent on both the probe’s inductive and resonance electronic properties in a 60:40 ratio. This important data indicates that the reaction of DPBF with singlet oxygen undegoes a more complicated mechanism than the commonly accepted concerted [4+2] Diels-Alder cycloaddition and enables the potential designs of more reactive probes.